2022
DOI: 10.3389/fchem.2022.1001531
|View full text |Cite
|
Sign up to set email alerts
|

Towards two-dimensional color tunability of all-solid-state electrochromic devices using carbon dots

Abstract: Electrochromic devices (ECDs) that display multicolor patterns have gradually attracted widespread attention. Considering the complexity in the integration of various electrochromic materials and multi-electrode configurations, the design of multicolor patterned ECDs based on simple approaches is still a big challenge. Herein, it is demonstrated vivid ECDs with broadened color hues via introducing carbon dots (CDs) into the ion electrolyte layer. Benefiting from the synergistic effect of electrodes and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As can be seen, the color of the ECD with various systems could be synthetically tuned to produce a large family of multicolor states during potentiostatic charge/discharge cycling. Moreover, in previous work, we found that adding the carbon dots (CDs) into the electrolyte layer of the ECD can also greatly enrich the color of the ECD Figure b displays the optical images of ECDs (PB-WO 3 system) containing different CDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the color of the ECD with various systems could be synthetically tuned to produce a large family of multicolor states during potentiostatic charge/discharge cycling. Moreover, in previous work, we found that adding the carbon dots (CDs) into the electrolyte layer of the ECD can also greatly enrich the color of the ECD Figure b displays the optical images of ECDs (PB-WO 3 system) containing different CDs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in previous work, we found that adding the carbon dots (CDs) into the electrolyte layer of the ECD can also greatly enrich the color of the ECD. 45 Figure 5b displays the optical images of ECDs (PB-WO 3 system) containing different CDs. Obviously, with the increase of CDs, the color gradually changes from light yellow to orange red at the voltage of −1 V. When the mass of CDs decreased, the color of the ECD can change from blue to blackish green and deepen as the CDs decreased.…”
Section: Resultsmentioning
confidence: 99%
“…An ECD was successfully fabricated by employing MnO 2 and PB as complementary electrodes and meanwhile introducing CDs into the electrolyte layers. 125 The device initially appeared orange-red at 0 V, but with increasing voltage, its color transitioned gradually from orange-red to orange, light yellow, yellow, green, and finally to dark green (Fig. 17a).…”
Section: Strategies Of Multicolormentioning
confidence: 99%
“…In the devices, electrochromic materials are the core components, and their reversible optical properties can be achieved via regulating voltages. [13][14][15][16] Various organics (conducting polymers), 11,17,18 inorganics (metal oxides), [19][20][21] organometallic compounds 22 have been proficiently used for electrochromic materials, but the tendency to develop new electrochromic materials is still fierce. One of the important reasons to explore new materials is that the properties of current solid-state ECDs are severely limited.…”
mentioning
confidence: 99%